ChemInform Abstract: The Liquid Junction Potential in Potentiometric Titrations. XII. The Calculation of Potentials for Emf Cells with Liquid Junctions, of the Type, AY / AY + A2MoO4 + HY, Involving the Formation of Iso‐Polymolybdates in the Range ‐Log10[H+] ≤ 7, at [A+] 0 C mol·L‐1, Constant, and 25 °C. Issue 1 (3rd January 2013) - Neher‐Neumann, Erzsebet
Abstract Review: 69 refs.